AGRICULTURAL WASTE PROCESSING TECHNOLOGY FOR RENEWABLE ENERGY IN MEXICO - Siti Aisyah; Liz Yanti Andriyani; Syaifullah Rahim; Zain Nizam (Techno Agriculturae Studium of Research, 2025)
This study aims to examine agricultural waste treatment technology as a renewable energy source in Mexico, focusing on the potential, challenges, and obstacles faced in its implementation. The background of this research is based on the large amount of agricultural waste produced by Mexico's agricultural sector, most of which has not been optimally utilized to produce renewable energy. The method used in this study is a descriptive-qualitative approach through secondary data analysis, interviews with experts, and case studies in some of the largest agricultural waste producing areas. The results show that although the energy potential of agricultural waste is huge, the rate of technology adoption is still low, due to technological, economic, and policy constraints. The conclusions of this study emphasize the importance of stronger policy support and the provision of adequate infrastructure to encourage wider adoption of waste treatment technology. Education to farmers and rural communities is also needed to increase awareness about the benefits of agricultural waste as an energy source.